Misinterpretation of the Qur'an: Thesis Analysis of Students of the Pontianak State Islamic Institute - Saifuddin Herlambang (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
This article analyzes the use of Qur'anic interpretation in the theses of early childhood education students at the Pontianak State Islamic Institute. This attracted the attention of the author because many students misinterpreted the verses of the Qur'an in the context of the research carried out by students. The entire thesis studied by the author shows the absence of references and the views of the interpreters regarding the verses used in the study. Of course, this is not in accordance with Islamic education research standards. The research method used by the author is qualitative, with a literature research approach. Data collection is carried out by analyzing or tracing student theses using Quranic verses. The data analysis used by the author is an analysis of the content of primary data and secondary data studied at the Pontianak State Islamic Institute. The results obtained in this study show that early childhood education students at the Pontianak State Islamic Institute still make many mistakes in interpreting verses from the Qur'an both from book citations to technical interpretations of qur'anic verses